Self awareness of a leader in Islamic management: ideal and possibility - Abdul Rashid, Adnan (2010)
Goodness and morality are the basic pillars that maintain the structure of every healthy organization or management. In this context, the Qur’an provides the ideal way of conduct, which is that a leader can attain moral perfection by righteous work (camal salih) and being of good character namely, muttaqi leader. Having a good character ensures that a leader behaves properly towards other members of undertaken organisation and this will keep social order in management. Din-al-Islam, explicitly cultivates in every Muslim leader the awareness of accountability and responsibility before Allah which is very crucial for Islamic management. The sphere of awareness builds up sincerity in one’s life or a leader because one’s acts are actually free of external forces, and merely for Allah’s pleasure. He also nourishes a life of virtues such as piety, patience, always seeks repentance, truthfulness, fear, hope and love of Allah, reliance on Allah, thankful praise and so on. In fact, this sensitivity may avoid source of evils or corruptions from all sort of management. The awareness of accountability is one of the elements of Islamic tarbiyyah which may form the individual leadership responsibility. This tarbiyyah begins for everyone at the age of baligh (puberty) when he or she is supposed to shoulder responsibility as prescribed in the Sharicah and bear the consequences of all his or her deeds. If a leader is devoid or unaware of the sense of accountability and responsibility before Allah, he or she actually may get involved in sin and corruption. The beneficent tarbiyyah of a sense of accountability and responsibility may nourish a leader’s relationship of complete obedience and trust in Allah. More significantly, a leader who understands and realises his responsibilities and is mindful of these will act and behave in a good manner with a firm Iman and develop a strong relationship with Allah. This may enable a leader to carry out his acts and commitments in all spheres of management in an orderly way, to seek virtue by all possible means, to behave positively rather than destructively whether privately or publicly, and to correct his mistakes and repent from his sins. If a leader practises this tarbiyyah, then the door which leads to corruption in management should stay shut, and the possibility that he or she will commit a bad deed or corruption is very low and rather rare. This concept paper attempts to examine and discuss the ideals of self-awareness and the efforts how self-awareness creates an atmosphere where every individual leadership feels ashamed of his evil deeds, is responsible for his actions to himself and others, and is aware of the punishment in the Hereafter for the sins and corruptions committed. If this attitude is embedded in every individual leader, then a righteous environment in organisation or management will eventually emerge and all sort of management will be efficiently go through.